Land transport development in three integrated scenarios for Germany – Technology options, energy demand and emissions. (January 2021) - Ehrenberger, Simone; Seum, Stefan; Pregger, Thomas; Simon, Sonja; Knitschky, Gunnar; Kugler, Ulrike
Graphical abstract: Comparison of overall CO2 emissions of land transport in the three scenarios. Highlights: The impact of political and economic actions on land transport is quantified. The contribution of technical improvements in vehicle technology on transport emissions is shown. Changes in energy sector are mandatory to lower overall transport induced emissions. A substantial emission reduction in 2040 requires political measures now. Abstract: Today, transportation contributes significantly to greenhouse gas emissions and air pollution. However, new technologies are emerging and existing technologies are being further improved. This article presents the results of a comprehensive study on the development of drive-trains, resulting electricity and fuel consumption as well as emissions of CO2 and selected air pollutants in land transport in Germany. This includes a quantitative assessment of technological potentials and of resulting energy consumption and emissions. The scenario building followed an explorative approach. Only the scenario depicting a consistent transition towards electrified mobility and regulated emissions from the energy system leads to a significant reduction in transport related CO2 emissions. Yet, the analysis shows that it is unlikely that the German emission reduction target in 2030 for the transport sector will be met. Nevertheless, the integrated scenario analysis demonstrates that only a joint de-carbonization of both transport and electricity systems lead to a significant reduction of emissions.